Inadequate binding of immune regulator factor H is associated with sensitivity of Borrelia lusitaniae to human complement - Dieterich, Roswitha; Hammerschmidt, Claudia; Richter, Dania; Skerka, Christine; Wallich, Reinhard; Matuschka, Franz-Rainer; Zipfel, Peter F.; Kraiczy, Peter (Infection and immunity, 2010)
Spirochetes belonging to the Borrelia burgdorferi sensu lato complex differ in resistance to complement-mediated killing by human serum. Here, we characterize complement sensitivity of a panel of B. lusitaniae isolates derived from ticks collected in Germany and Portugal as well as one patient-derived isolate, PoHL. All isolates are highly susceptible to complement-mediated lysis in human serum and activate complement predominantly by the alternative pathway, leading to an increased deposition of complement components C3, C6, and the terminal complement complex. Interestingly, serum-sensitive B. lusitaniae isolates were able to bind immune regulator factor H (CFH), and some strains also bound CFH-related protein 1 (CFHR1) and CFHR2. Moreover, CFH bound to the surface of B. lusitaniae was inefficient in mediating C3b conversion. Furthermore, the identification and characterization of a potential CFH-binding protein, OspE, revealed that this molecule possesses a significantly reduced binding capacity for CFH compared to that of CFH-binding OspE paralogs expressed by various serum-resistant Borrelia species. This finding suggests that a reduced binding capability of CFH is associated with an increased serum sensitivity of B. lusitaniae to human complement.
Gesehen am 17.05.2021